How Does Psychological Contract Mediate the Effect of Transformational Leadership on Job Satisfaction? Moderating Variable of Tenure - Nailatul Muhajiroh; Noermijati Noermijati (Khazanah Sosial, 2024)
This research investigates how the role of the mediating variable of psychological contract and the moderating variable of tenure on the influence of the independent variable of transformational leadership on job satisfaction in Indonesian government organizations. This research is in line with Decker, (2018) the results of the study show that transformational leadership significantly affects job satisfaction, this is also expressed in research. Masal, (2015) with the title "Shared and transformational leadership in the police" shows that transformational leadership exerts a significant influence on shared leadership and has a significant influence on organizational goals and creates job satisfaction for followers. Quantitative was used for data analysis and questionnaires as a data collection technique distributed online using Google Forms to all employees of civil servants in the Indonesian government with a simple random sampling technique. Data analysis using SEM-PLS with the help of applications, namely SmartPLS. This study shows the results that the independent variable of transformational leadership has a significant influence on the dependent variable of job satisfaction. Directly, the psychological contract promotes increased job satisfaction. The psychological contract acts as a partial mediation on the influence of transformational leadership on job satisfaction. The moderating variable of tenure also plays a role in strengthening the influence of the independent variable of transformational leadership on job satisfaction.